Developing the crypto-waqf model: a perspective for entrepreneurs’ sustainability - Muhammad Zuki, Mohd Faizuddin; Abdul Rahim, Razinda Tasnim; Md Noor, Nur Syamilah (RSIS International, 2025)
Waqf is a unique Islamic philanthropic instrument for social development, revealed to Prophet Muhammad PBUH 1400 years ago. Properly managed waqf property and funds can boost economic growth, stabilize the economy, and alleviate poverty by financing entrepreneurs and small to medium-scale enterprises. On the other hand, integrating financial matters and technology has enhanced and increased productivity. As such, integrating waqf and cryptocurrency would provide new Islamic social finance instruments and benefit society in general and specifically for entrepreneurs’ sustainability. Therefore, this paper proposes a practical model for crypto-waqf with its modus operandi. This study employed extensive qualitative research methods through semi-structured expert interviews to achieve the intended research objective. The proposed model of cryptowaqf is presented in the study’s findings. This study implies that it benefited waqf institutions such as MAINs in adopting the crypto-waqf model for their services.